A novel single nucleotide polymorphism in the protein tyrosine phosphatase N22 gene (PTPN22) is associated with Type 1 diabetes in a Chinese population. Issue 2 (21st October 2013) - Pei, Z.; Chen, X.; Sun, C.; Du, H.; Wei, H.; Song, W.; Yang, Y.; Zhang, M.; Lu, W.; Cheng, R.; Luo, F.
Abstract Aims To examine single nucleotide polymorphisms in the protein tyrosine phosphatase N22 gene (PTPN22) and to study their association with Type 1 diabetes in a Chinese cohort. Methods Three hundred and sixty‐four young patients with Type 1 diabetes and 719 healthy children were included in this case‐controlled study. The genotypes of rs1217385, rs2488457 (–1123C>G), rs1217414, rs1217419, rs3765598 and rs2476601 (1858C>T) in the PTPN22 gene were determined using the SNaPshot method. Alleles, genotypes and haplotype frequencies were compared between patients with Type 1 diabetes and healthy control subjects. The association between single nucleotide polymorphisms and clinical traits/autoantibody status was also analysed. Results The single nucleotide polymorphism, rs1217419, located in the second intron of the PTPN22 gene was associated with Type 1 diabetes (odds ratio 1.5, 95% CI 1.14–1.97, P = 0.003). An additional single nucleotide polymorphism, rs1217385, was also associated with Type 1 diabetes; however, the association was secondary to that of rs1217419. The previously reported single nucleotide polymorphism that is associated with Type 1 diabetes (–1123G>C) had only marginal association with Type 1 diabetes in our study. A marginal association was also identified between –1123G>C and glutamic acid decarboxylase autoantibody positivity in patients with Type 1 diabetes. There was no association between the single nucleotide polymorphism 1858C>T and Type 1 diabetes in our studied cohort. Conclusions Our study confirmed that PTPN22 is a gene that contributes to Type 1 diabetes susceptibility. The primary association occurs with single nucleotide polymorphism rs1217419 and there is clear heterogeneity of the association between PTPTN22 polymorphisms and Type 1 diabetes in a Chinese population compared with other populations.